Hemophagocytic lymphohistiocytosis - A fatal cause of persistent fever in neonates: A case series - Pillai, Anupama Sasidharan; Rahul, Aswathy; Hariharan, Sankar V; Sujatha, Radhika; Gopal, Athulya (Indian Journal of Child Health, 2022)
Primary hemophagocytic lymphohistiocytosis (HLH) is a rare fulminant genetic disease with uncontrolled immune activation and multiorgan involvement. It is quite rare in neonates but a high index of suspicion is needed as the condition will present like sepsis and is associated with high mortality. Persistent fever is a prominent clinical feature. Genetic diagnosis is essential as the condition is autosomal recessive in familial types. Here, we report four cases of HLH diagnosed in the newborn period. We got an uncommon homozygous genetic mutation in STXBP2 involving exon 19, which has been reported only in very few cases. HLH should be considered as a differential diagnosis in any sick neonate who presents with prolonged fever with an unusual clinical course